Factors affecting achmad yani university's student management departement acceptance of young consumers for mobile marketing - Aam Rachmat Mulyana; Ratih Hurriyati; Puspo Dewi Dirgantari (Institute of Computer Science (IOCS), 2022)
All Indonesians have become cellular phone subscribers or have cell phone numbers, and many of them have more than one cell phone number. The majority of cellular telephone subscribers in Indonesia subscribe to prepaid services with a total of 345.95 million subscribers. Indonesian population in terms of hours spent using mobile devices, the average time spent by Indonesian mobile users has increased by 38% from 2020. Mobile users in Indonesia have downloaded 7.31 billion applications. That means, every 1 minute, more than 13 thousand applications are downloaded by mobile users in Indonesia. This phenomenon indicates that companies must consider the potential acceptance of mobile marketing to be used as a business strategy and researchers are interested in researching it. The purpose of this study is to describe the factors that influence the mobile marketing acceptance variable. The research method uses quantitative methods with descriptive analysis. The research sample is 151 respondents. The results of the study show that personal attachment has a significant positive effect on sharing content, sharing content has a significant positive effect on mobile marketing acceptance, risk acceptance has a significant positive effect on providing information.